New uses for old drugs: neonatal diabetes and sulphonylureas. - Ashcroft, F (2010)
The discovery that their neonatal diabetes is caused by gain-of-function mutations in the K(ATP) channel has enabled many patients to switch from insulin to oral sulphonylurea drugs. Here, I review molecular, physiological, and clinical features of this change in therapy.